PEMANFAATAN MUSEUM ISDIMAN AMBARAWA SEBAGAI SUMBER BELAJAR - Dratiarawati, Aninda (Indonesian Journal of History Education, 2015)
This study aims to prove the existence of differences in student interest between classes using Isdiman Museum Ambarawa as a learning resource with a class that does not use Isdiman Museum Ambarawa as a learning resource. This research is a quantitative research with experimental design. The population in this study is a class XI student high school Ambarawa. The samples in this study using simple random sampling technique with a design pretest-posttest control group design. The sample was a class XI student of social science as a control class and class XI student of social sciences is the experimental class. Â